PENGADAAN TANAH UNTUK PEMBANGUNAN ALUN-ALUN KOTA DEPOK BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2012: Land Acquisition for the Construction of Depok City Square Based on Law Number 2 of 2012 - Affandi, Fiorello Ghali; Cahyana, Intan Nevia (Faculty of Law, Universitas Trisakti, 2024)
This research aims to evaluate the land acquisition process carried out by the Depok City Government for the development of Alun-Alun Kota Depok. The main question under investigation is the extent to which this land acquisition complies with the provisions stipulated in Law Number 2 of 2012 concerning Land Acquisition for Development for Public Purposes and National Land Law. The research methodology employed is normative legal research with a qualitative and descriptive approach, utilizing secondary data, and applying deductive methods to draw conclusions. The research results indicate that the land acquisition for the development of Alun-Alun Kota Depok has adhered to the applicable regulations, including Law Number 2 of 2012 concerning Land Acquisition for Development for Public Purposes and other National Land Law regulations. Therefore, it can be concluded that the development of Alun-Alun Kota Depok is in accordance with the prevailing legal provisions and does not face significant legal obstacles in its implementation